Model Inklusi Silinder dalam Jaringan Homogen untuk Elastografi Biomedik - Idam Arif; Astalini Astalini (Jurnal Matematika & Sains, 2005)
A cylindrical inclusion model in a tissue matrix is proposed for biomedical elastography. Solutions of elasticity equation are applied to observe the effects of the inclusion on the distribution of a uniform stress given to the matrix. The inclusion and the matrix are assumed to be isotropic, homogen, and linear. The obtained analytical solutions are illustrated in the form of graphics for breast tumors and cysts. It is shown that the effects are located in the region less than 3R, with R being the inclusion radius. If the inclusion is stiffer than the matrix (µb>µt), then the displacement in z direction is negative and is positive in y direction. It means that the strain and stress components in z direction (ezz,szz) are negative and (eyy,syy) are positive in y direction. If the inclusion is softer than the matrix (µb>µt) then the displacement in z and y directions is negative. Therefore the strain and stress components in z direction and in y direction both are also negative.